2019
DOI: 10.4103/iju.iju_91_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of percentage free PSA, MRI and GaPSMA PET scan for diagnosing cancer prostate in men with PSA between 4 and 20 ng/ml

Abstract: Introduction: We compared the diagnostic accuracy of percentage free prostate-specific antigen (PSA), multiparametric magnetic resonance imaging (mpMRI), and gallium-68 prostate-specific membrane antigen positron emission tomography (Ga-PSMA PET) to detect cancer prostate in men with PSA between 4 and 20 ng/ml in prebiopsy settings. Materials and Methods: This prospective study evaluated men with PSA values between 4 and 20 ng/ml, and all patients underwent percentage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…The superior diagnostic accuracy of the PSMA-PET scan compared to MRI and PET imaging alone in the detection of primary prostate cancer, its usefulness in screening, as well as guiding biopsies have been described in several independent studies (37)(38)(39).…”
Section: Introductionmentioning
confidence: 98%
“…The superior diagnostic accuracy of the PSMA-PET scan compared to MRI and PET imaging alone in the detection of primary prostate cancer, its usefulness in screening, as well as guiding biopsies have been described in several independent studies (37)(38)(39).…”
Section: Introductionmentioning
confidence: 98%
“…After initial screening according to titles, eligible criteria, and removal of duplicates, a total of 25 articles were selected. Of these, 18 were finally included and downloaded in a full-text version [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. No further studies were added after examination of the references of these articles ( Figure 1 : PRISMA flowchart of the study).…”
Section: Resultsmentioning
confidence: 99%
“…Two experienced nuclear medicine specialists always interpreted results by consensus. In 8 articles, there was a direct comparison with MRI [ 22 , 23 , 26 , 28 , 31 , 32 , 33 , 35 ]. In 7 of them, MRI scans were acquired on 3.0 Tesla (T) MRI by four sequences: T1-weighted imaging, T2-weighted imaging, fat-suppression presaturation-attenuated inversion recovery, and diffusion-weighted imaging (DWI); PI-RADS v2.0 was used for reporting images in all of them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another recent study showed that Ga-PSMA PET scan has a higher NPV and accuracy than mpMRI in detecting tumor foci within the prostate. [ 16 ] There are reports where targeted biopsy using PSMA PET/CT is being explored with success. [ 17 ] This may be more beneficial in cases which are equivocal on serum PSA and mpMRI.…”
Section: Discussionmentioning
confidence: 99%